(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
The problem of using project work in teaching Uzbek is of great importance. Project work is characterized as one of the most effective methods of teaching and learning the language through research and communication, different types of this method allow us to use it in all the spheres of the educational process. It involves multiskill activities which focus on a theme of interest rather than of specific language tasks and helps the students to develop their imagination and creativity. Nevertheless, teachers are not keen on the idea of providing project work into their lessons because of the disadvantages this method has. The main idea of project work is considered to be based on teaching students through research activities and stimulating their personal interest.